The effectiveness of group counseling based on islamic value to reduce the late behaviour of students - Abdi, Sofyan; Wibowo, Dwi Endrasto; Sa'adah, Sa'adah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
Discipline is a positive and constructive force in shaping children's character related to the environment; the application of disciplinary values must be carried out continuously, to achieve all expected goals. The purpose of this study was to determine the effectiveness of Islamic value-based group counselling to reduce students' late behaviour. The instrument used in this study was a late behaviour questionnaire. The research was conducted at one of Budi Mulia Utama Senior High School in East Jakarta, with 8 students as the research subject. The design that will be used is one group pretest-posttest design. The results of the t-test data analysis showed that Islamic value-based group counselling was effective in reducing students' late behaviour. The findings in the field show that students' late behaviour has decreased after being given group counselling services. Group counselling is carried out by internalizing Islamic values related to discipline in service content at each stage of its implementation. Cultivating Islamic values builds children's awareness of discipline and values time and forms a responsible character.